Osteonecrosis as a rare musculoskeletal complication in Behcet’s disease- the largest case series with literature review - Mohammad Nejadhosseinian; Mazyar Babagoli; Seyedeh Tahererh Faezi; Hoda Haerian; Farhad Shahram; Majid Alikhani; Fereydoun Davatchi (BMC Rheumatology, 2023)
Abstract Background Behcet disease (BD) as a variable vessel vasculitis is mainly characterized by ocular involvement, genital and oral aphthosis, and erythema nodosum. However, major organ involvements including gastrointestinal involvement, nervous system, and vascular involvement are among the severe complications. Osteonecrosis is a rare complication of patients with BD. We aim to report the largest series of BD patients suffering from osteonecrosis. Methods We have retrospectively reviewed all patients in Iran Behcet’s Disease Registry and reported those with osteonecrosis. Patients’ medication and clinical features, symptoms, and details of osteonecrosis will also be presented. Furthermore, previously reported cases will also be reviewed. Results Seven thousand eight hundred thirty-one patients were diagnosed with BD and registered. 18 patients developed ON with an incidence of 0.22%. The most common involvement during the disease progression was oral aphthosis which appeared in 100% of patients followed by ocular involvement in 85.7% and skin involvement in 71.4%. Vascular, ocular, and nervous system involvements are significantly higher in BD patients with osteonecrosis than the other BD patients. For the management of acute episode of uveitis, deep vein thrombosis, severe gastrointestinal involvement, arterial involvement, nervous system Involvement, and joint involvement high dose of glucocorticoids is indicated. Conclusions ON tends to appear as a multifocal involvement in BD patients, hence, after diagnosis of ON in one joint other possible sites of ON should be investigated.